Moraxella catarrhalis – An underestimated culprit for community-acquired lower respiratory tract infections in diseased adult lungs - Mallika Sengupta; Prashant Sharma; Sudip Ghosh; Sayantan Banerjee (Journal of Family Medicine and Primary Care)
In four months, five cases of Moraxella causing lower respiratory tract infection were encountered among patients with underlying lung disease in the Pulmonary medicine outpatient department of a tertiary care center in rural West Bengal. The patients exhibited a spectrum of clinical presentations, ranging from mild to severe respiratory symptoms along with shortness of breath as the most consistent symptom. Diagnostic workup revealed Moraxella catarrhalis as the causative agent of lower respiratory tract infections in all cases, highlighting its emerging role as a significant respiratory pathogen. Treatment strategies varied based on disease severity, but all the patients improved with treatment. These cases underscore the importance of considering Moraxella as a causative organism for community-acquired lower respiratory tract infection and emphasize the need for continued surveillance and research to better understand its epidemiology and clinical management.